A dual-targeting, apoptosis-inducing organometallic half-sandwich iridium anticancer complex - Novohradsky, Vojtech; Zerzankova, Lenka; Stepankova, Jana; Kisova, Anna; Kostrhunova, Hana; Liu, Zhe; Sadler, Peter J; Kasparkova, Jana; Brabec, Viktor (Metallomics, 2014)
The cellular mechanism of action of an iridium(III) half-sandwich complex [(η(5)-C5Me4C6H4C6H5)Ir(phen)Cl]PF6 (phen = phenanthroline) (1) is reported. Complex 1 was used to treat several cell lines, including cisplatin-sensitive, cisplatin-resistant (with intrinsic and acquired resistance) carcinoma cells with wild type p53 status as well as the cells with no intact p53 gene, and nontumorigenic cells. Complex 1 preferentially kills cancer cells over nontumorigenic cells and exhibits no cross-resistance with cisplatin. It appears to retain significant activity in human tumor cell lines that are refractory or poorly responsive to cisplatin, and in contrast to cisplatin it displays a high activity in human tumor cell lines that are characterized by both wild type and mutant p53 gene. The mechanism of cell killing was established through detailed cell-based assays. Complex 1 exhibits dual effects in killing cancer cells causing nuclear DNA damage and mitochondrial dysfunction involving ROS production simultaneously. Flow cytometric studies and impedance-based monitoring of cellular responses to 1 demonstrated that 1 acts more quickly than cisplatin to induce cell death and that 1 is a more effective apoptosis inducer than cisplatin in particular in early stages of treatment, when the apoptotic effects predominate over necrosis. Overall, our findings confirm that 1 and its iridium derivatives represent promising candidates for further pre-clinical studies and new additions to the growing family of nonplatinum metal-based anticancer complexes.
Keywords: apoptóza; Reactive Oxygen Species; cisplatina; Iridium; iridium; průtoková cytometrie; nádorové buněčné linie; lidé; protinádorové látky; Cisplatin; Cell Line, Tumor; Humans; reaktivní formy kyslíku; Antineoplastic Agents; Flow Cytometry; Apoptosis